Temperament Types And Their Characteristics In Psychology - Mustafokulova Madina Shomurod kizi (Euro Asian Journal Publishing, 2025)
This article analyzes the psychological foundations of temperament, the history of its study and its types, the specific characteristics of each type. Temperament is the main biological factor governing a person's mental activity and has a strong influence on his vital activity. Each type of temperament is manifested by different behavior and emotional reactions.
Keywords: Temperament; choleric; sanguine